Implementation of markov chain in predicting regeneration agricultural in Pasuruan district - Abdul Wahid; Ayik Pusakaningwati; M. Imron Masud (SAINTIS Publishing, 2022)
The Industrial Era 5.0 has made many positive and negative changes in various sectors, one of the negative impacts is the agricultural sector related to the lower portion of young farmers so that it must be a serious concern for the government in future agricultural development programs, especially in agricultural base areas such as in Pasuruan Regency. This situation encourages the importance of finding solutions to realize the regeneration of farmers. This study aims to analyze the transformation between generations of agricultural workers in Pasuruan Regency through the Marcov Chain model approach. The final result of this study is the analysis of transformations between generations of agricultural workers in Pasuruan Regency so that it can be used as a basis for formulating future policies for better future generations of agriculture.